Peran Media Digital dalam Menyatukan Pandangan Masyarakat dan Pemerintah untuk Mewujudkan Smart City Medan - Rio Irawan Munthe; Putri Nabila; Dermawan Wijaya Harahap; Ahmad Tamrin Sikumbang (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Digital media is currently the main key to public communication to convey aspirations in government policies. Medan is also one of the major cities in Indonesia that is striving to realize the concept of a smart city through digital media. The role of digital media is very important in realizing a smart city. This study aims to analyze how digital media plays a role in uniting the views of the community and the Medan city government in the effort to realize a smart city in Medan. The method used in this study is a qualitative descriptive approach with a library research approach and observation of digital communication activities, online news, and public statements from the government to the public in Medan. In realizing a smart city, optimizing digital communication is essential to strengthen the synergy between the community and the government. The results of the study indicate that digital media plays a crucial role as a means of two-way communication, information dissemination, and as a medium for public participation. However, challenges such as weak digital literacy and limited infrastructure are obstacles to the sustainability of this effort.